2018
DOI: 10.1080/2000656x.2018.1498790
|View full text |Cite
|
Sign up to set email alerts
|

Factors that predict deep inferior epigastric perforator flap donor site hernia and bulge

Abstract: Deep inferior epigastric artery perforator (DIEP) flap has become the gold standard in autologous breast reconstruction. Attention is now being focused on the impact of DIEP flap harvest technique on abdominal hernia rates. The aim of this study was to evaluate DIEP abdominal wall morbidity in relation to flap harvest and fascial closure technique. A retrospective analysis of patients undergoing DIEP flap breast reconstruction between 2012 and 2016 was performed. Post-operative evaluation of the abdominal wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 35 publications
3
29
1
Order By: Relevance
“…Our incidence of 7% is well in line with these studies. Similar to previous studies, we could observe a significant correlation between abdominal bulge and two or more perforators 11 . Considering that the dissection of a flap, based on two perforators, will harm the rectus fascia to a greater extent, an impairment on abdominal wall integrity seems plausible.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our incidence of 7% is well in line with these studies. Similar to previous studies, we could observe a significant correlation between abdominal bulge and two or more perforators 11 . Considering that the dissection of a flap, based on two perforators, will harm the rectus fascia to a greater extent, an impairment on abdominal wall integrity seems plausible.…”
Section: Discussionsupporting
confidence: 89%
“…We further observed an increased incidence of abdominal bulge in patients with a higher BMI. Although a similar correlation was reported by other authors, a higher BMI might bias the need for two or more perforators 11,17 . It is well known that the contribution of the deep and the superficial system to the perfusion of the lower abdomen is inversely related 18,19 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It is imperative, however, to educate all the patients of this potential risk and a possible increased risk of hernias due to fascial dehiscence. 35…”
Section: Respiratory Complicationsmentioning
confidence: 99%
“…When a perforator from the DIEA has to be included, the dissection is limited to its take off point, with a small T‐portion obtained from the DIEA. Butler et al (2018) reported in their retrospective analysis of 234 DIEP flaps that taking a single perforator was less likely to result in postoperative hernia or bulging than taking two or more perforators. Thus, we believe our method minimizes the risk of postoperative herniation and bulging.…”
Section: Discussionmentioning
confidence: 99%